2013
DOI: 10.1124/mol.112.083352
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic Glutamate Receptors: Regulation by G-Protein-Coupled Receptors

Abstract: The function of many ion channels is under dynamic control by coincident activation of G-protein-coupled receptors (GPCRs), particularly those coupled to the G as and G aq family members. Such regulation is typically dependent on the subunit composition of the ionotropic receptor or channel as well as the GPCR subtype and the cell-specific panoply of signaling pathways available. Because GPCRs and ion channels are so highly represented among targets of U.S. Food and Drug Administration-approved drugs, function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…AMPARs are composed of four types of subunits: GluR1-4. Through autocrine glutamate signaling, they contribute to enhanced glioma cell invasion (112,113). The subunits, especially GluR2, influence the cation permeability of AMPAR.…”
Section: Ion Channels and Their Contribution To Glioma Cell Migrationmentioning
confidence: 99%
“…AMPARs are composed of four types of subunits: GluR1-4. Through autocrine glutamate signaling, they contribute to enhanced glioma cell invasion (112,113). The subunits, especially GluR2, influence the cation permeability of AMPAR.…”
Section: Ion Channels and Their Contribution To Glioma Cell Migrationmentioning
confidence: 99%
“…It was previously demonstrated that PKC-mediated phosphorylation of GluK2 C-terminal residues Ser-846 and Ser-868 regulates the recycling of GluK2 to the plasma membrane (19,(22)(23)(24). This led us to predict that if we promoted PKC-mediated GluK2 phosphorylation, we would also regulate KCC2 recycling.…”
Section: Pkc-mediated Phosphorylation Of Gluk2 Is Required For Gluk2 mentioning
confidence: 99%
“…Glutamate binds to post-synaptic glutamate receptors, including ionotropic glutamate, kainate, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), and N-methyl-D-aspartate (NMDA) receptors [18]. Glutamate-induced excitotoxicity is considered an important mechanism underlying neuronal death in ischemia, CNS trauma, and epilepsy [19].…”
Section: Glutamatementioning
confidence: 99%